Pemisahan Logam Tanah Jarang dari Limbah (Tailing) Emas Poboya dengan Metode Pengendapan: Separation of Rare Earth Metals from Poboya Gold Waste (Tailings) by Deposition Method - Arianto; Husain Sosidi; Prismawiryanti; Dwi Juli Pusptasari (KOVALEN: Jurnal Riset Kimia, 2020)
Gold tailings are waste generated from gold mining activities and contain minerals and rare-earth metals (REM) that are much needed in current technological developments. This research was conducted to determine the REM content contained in Poboya gold tailings, through the destruction process using sulfuric acid and precipitation using ammonium hydroxide. The results were showed that the level of REM contained in Poboya gold tailings was 6-7%. REM oxide content analysis performed with Scanning Electron Microscopy - Energy Dispersive X-Ray Spectroscopy (SEM-EDS) obtained 6 types of REM with the main REM levels namely Terbium (Tb): 77-80% dan Lanthanum (La): 13%, as well as other rare-earth metals with smaller amounts of Europium (Eu): 4-5%, Cerium (Ce): 2%, Neodymium (Nd): 0.02% and Gadolinium (Gd): 0.02%. Poboya gold waste can be used by the community as a source of REM and used in various industries. Keywords: Gold tailings, rare earth metals (REM), destruction, precipitation